Essays on climate change, wheat production, and adaptation strategies in Pakistan - Rub, Abdur (Kansas State University, 2023)
Pakistan is one of the most vulnerable countries to climate change and sustainable growth in its wheat supply holds one key to food security. Therefore, the purpose of this research is to analyze the relationship between weather and wheat production in Pakistan and assess the adaptation possibility. The first paper, using district-level agricultural data spanning 37 years and covering more than 80% of wheat production in the country, provides estimates of the overall and intra-seasonal impacts of extreme temperature exposure. It finds that the impact of temperature extremes varies across different seasons such that the freezing temperatures in the fall season and warming of the winter season are found to be the biggest drivers of yield loss, with 16.7% and 8.8% yield reduction respectively. The future warming scenarios suggest overall mild gains in wheat yields. The second paper utilizes a richer farm-level dataset with 33,621 plot-year observations to estimate the warming impacts across irrigation status and explore heterogeneities across wheat varieties. It finds that warming temperatures are particularly harmful in rainfed conditions and irrigation provides significant protection against heat stress. estimating a 70% smaller yield reduction. Moreover, the paper examines the heterogeneity of temperature effects across wheat varieties and finds that newer varieties are associated with higher yields and more heat resistance. Further, variety selection is also found to have significant potential in mitigating the adverse impact of warming temperatures. The research aims to inform future research on the relationship between weather and wheat yields in Pakistan by providing evidence of the impact of temperature on wheat yields and measuring the effectiveness of possible adaptation measures.
Keywords: Food security; Climate change; Production economics; Pakistan; Wheat